THE INTEGRATION OF BALINESE LOCAL WISDOM INTO THE INFORMATION TECHNOLOGY SUPPORTED-GENERATIVE MODEL - I Putu Pasek Suryawan (Universitas Pendidikan Ganesha, 2017)
This research aimed at increasing students’mathematical proving ability through the implementation of the Generative Model based on local wisdom assisted by video learning on Khan Academy website. The subjects of this Classroom Action Research were 30 students in class II B of the Department of Mathematics Education Universitas Pendidikan Ganesha in the year of 2015/2016. This research was completed in 2 cycles with the steps of each cycle were planning, treatment action, observation and evaluation, and reflection. The data was analyzed descriptively. The result shows that the students’ mathematical proving ability was increased from the average 13.20 in enough category in cycle I to the average 15.83 in the high category in cycle II. Therefore, the implementation of generative model based on local wisdom assisted by video learning in Khan Academy website increase the students’ mathematical proving ability.